IMPLEMENTATION OF SUPPORT VECTOR REGRESSION FOR PREDICTING LAWYER CHARGES USING CLOUD COMPUTING IN GOOGLE COLAB - Ilmiyati Sari; Rifki Kosasih; Dina Indarti (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
In court, the role of the lawyer is needed by the defendant in carrying out the defense. In various legal cases, lawyers are able to assist and accompany their clients until the judge's decision is rendered. However, lawyer charge can vary depending on several factors. This research proposes 3 factors that can affect attorney fees. i.e., length of sentence, type of case and distance of lawyer's office to Jakarta district court. The data used in this study is 100 judge's decision data originating from the website of the Jakarta district court. Then the data is divided into two parts with 80 data for training data and 20 for test data. In this study, we predict the lawyer charge by implementing Support Vector Regression (SVR) method in Google Colab. Based on results of this research, we found that the value of Mean Square Error (MSE) was 0.401, the value of Mean Absolute Error (MAE) was 0.347, and the value of Root Mean Square Error (RMSE) was 0.633.